The partisan lens: analyzing news media's role in political polarization through coverage of Trump's initiatives against DEI within his first week of presidency in 2025 - Juba, Malia, author; Anderson, Karrin, advisor; Marx, Nick, committee member (Colorado State University. Libraries, 2025)
Political polarization has become entrenched in American citizens' political culture, altering how people ideologically think, associate with certain issues, and interact with the people and politics surrounding them. This literature review and case study examine how modern news media contribute to political polarization in the US through a case study on coverage of President Trump's first week in office (2025). To do so, I first review existing literature surrounding the origins of political polarization, the role of contemporary media, and how political polarization exists and operates in the twenty-first century. Next, I analyze this phenomenon through two distinctly partisan news outlets and their coverage of President Trump's first week in office and his early efforts to federally dismantle DEI programs. The findings of this study conclude that traditional news media's framing, language, and themes can contain partisan bias. This study contributes to the field of political communication by providing insight into the ways in which media frames political events and shapes public perception, particularly in the context of a highly contentious incident.
Keywords: polarization; media; newspaper; partisan; framing